Automatic grid adaptation for unstructured finite volumes. (1st March 2010) - Wackers, J.; Visonneau, M.; Ali, Z.
An automatic grid refinement method is presented for the simulation of ship flows. It provides directional refinement of unstructured grids and derefinement of refined grids for unsteady simulation, it is fully parallel and includes automatic dynamic load balancing. Different refinement criteria are implemented. Results are presented that confirm the increased accuracy of solutions obtained on refined grids. Refinement around the water surface proves to be very effective for the simulation of strong breaking waves. A pressure gradient criterion is shown to detect the main features of a ship flow and to be able to generate effective fine grids in their entirety.